2021
DOI: 10.1515/jpm-2020-0402
|View full text |Cite
|
Sign up to set email alerts
|

The neonatal respiratory morbidity associated with early term caesarean section – an emerging pandemic

Abstract: Objectives To examine the impact of early term caesarean section (CS) on respiratory morbidity and early neonatal outcomes when elective caesarean section was carried out before 39 completed weeks gestation in our population. Methods A one-year population-based retrospective cohort analysis using routinely collected hospital data. Livebirths from women who had elective lower segment cesarean section (ELSCS) for uncomplicated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 17 publications
2
6
0
3
Order By: Relevance
“…This study also showed that early‐term birth was associated with an increased risk of respiratory distress among neonates delivered via cesarean delivery at term with no indications for early delivery. This result is consistent with previous studies that showed the effects of early‐term birth on neonatal respiratory morbidity 34 , 35 and highlights the significance of the increasing frequency of early‐term births on neonatal health.…”
Section: Commentsupporting
confidence: 93%
“…This study also showed that early‐term birth was associated with an increased risk of respiratory distress among neonates delivered via cesarean delivery at term with no indications for early delivery. This result is consistent with previous studies that showed the effects of early‐term birth on neonatal respiratory morbidity 34 , 35 and highlights the significance of the increasing frequency of early‐term births on neonatal health.…”
Section: Commentsupporting
confidence: 93%
“…The most common adverse outcome was neonatal jaundice which accounted for 66.4% with mean peak bilirubin value of 14.1.mg/dl followed by respiratory morbidity which accounted for 28%. A study done by Ghartey K et al showed that there is 2 fold increase in incidence of respiratory morbidity in early term neonates when compared to term neonates [14] and this fact is also supported by the study done by Thomas J et al [15]. The increase in respiratory morbidity is probably due to decreased clearance of lung fluid which is secondary to delayed pulmonary fluid absorption due to decreased maturity and increased rate of LSCS.…”
Section: Discussionmentioning
confidence: 78%
“…Respiratory distress occurs in 7% of the term newborns [ 20 ]. Elective caesarean delivery prior to full term increases the risk of respiratory morbidities [ 21 , 22 ]. Risk factors for transient neonatal distress are elective caesarean, preterm delivery, male sex, low birth weight and maternal conditions such as asthma and gestational diabetes [ 20 , 23 – 25 ].…”
Section: Discussionmentioning
confidence: 99%